Foliar macronutrient contents and maize (Zea mays L.) production in response to gypsum application in an oxisol - Minato, Evandro Antonio; Esper Neto, Michel; Sakurada, Rodrigo Lima; Inoue, Tadeu Takeyoshi; Batista, Marcelo Augusto (Scientia Agraria Paranaensis, 2017)
The application of agricultural gypsum to the soil provides a favorable environment for the root development. It supplies the subsurface layers with elements such as calcium and sulfur and reduces the toxic aluminum activity. The objective of this study was to evaluate the influence of gypsum doses application on the maize (Zea mays L.) yield and the nutrients content of the leaves. The study was conducted in Terra Roxa city, Paraná State, Brasil, in an Oxisol. The experimental design was the randomized blocks with four replicates. The treatment were composed of four doses of gypsum (0; 3.0; 6.0 and 9.0 t ha-1) applied after the corn sowing. At the R1 phenological stage, the leaves were collected and the N, P, K, Ca, Mg and S levels were analyzed. After the physiological maturity, the plots were harvested for the productivity determination. The grain moisture was adjusted to 13%. The nitrogen, P and S foliar contents increased according to the gypsum doses increasing. On the other hand, K, Ca and Mg foliar content did not respond significantly to the gypsum application. The corn yield increased with the application of gypsum to the dose of 6.22 t ha-1, providing an increase of 17.8% in relation to the control.